1996
DOI: 10.1074/jbc.271.5.2365
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ob Gene in Adipose Cells

Abstract: The product of the recently cloned mouse obese (ob) gene is likely to play an important role in a loop regulating the size of the adipose tissue mass. The hormonal regulation of the ob gene could affect adiposity. To investigate this point, the effect of insulin on ob gene expression was examined in cells of the 3T3-F442A preadipocyte clonal line. ob mRNA is absent from exponentially growing, undifferentiated cells as well as from confluent preadipose cells. Terminal differentiation of preadipose to adipose ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
161
6
7

Year Published

1997
1997
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(187 citation statements)
references
References 27 publications
(28 reference statements)
12
161
6
7
Order By: Relevance
“…Our studies cannot rule out other indirect modes of insulin action on leptin, for instance, metabolic processes requiring insulin and glucose such as lipogenesis. In animals there is strong evidence in favor of direct effects of insulin on ob gene expression (22)(23)(24)(25)(26). Dose-dependent stimulation by insulin of ob gene expression has been shown in rat adipocytes in primary culture (22), cultured 3T3-F442A and 3T3-L1 mouse cells (23,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies cannot rule out other indirect modes of insulin action on leptin, for instance, metabolic processes requiring insulin and glucose such as lipogenesis. In animals there is strong evidence in favor of direct effects of insulin on ob gene expression (22)(23)(24)(25)(26). Dose-dependent stimulation by insulin of ob gene expression has been shown in rat adipocytes in primary culture (22), cultured 3T3-F442A and 3T3-L1 mouse cells (23,25).…”
Section: Discussionmentioning
confidence: 99%
“…In animals there is strong evidence in favor of direct effects of insulin on ob gene expression (22)(23)(24)(25)(26). Dose-dependent stimulation by insulin of ob gene expression has been shown in rat adipocytes in primary culture (22), cultured 3T3-F442A and 3T3-L1 mouse cells (23,25). Furthermore, it has been shown that raising or lowering of plasma insulin concentrations in vivo in rodents resulted in up-or down-regulation, respectively, of leptin mRNA, and that insulin produced a dosedependent rise in leptin release from cultured human fat cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results also suggest that, in women, the association between plasma leptin and insulin concentrations is independent of adiposity, a finding which provides further support to the observation that adipose tissue leptin secretion may be upregulated by insulin. [Diabetologia (1997) 40: 1178-1184] believed to be regulated by insulin both in vivo and in vitro [3,13,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is secreted by white adipose cells and is exclusively expressed in adipose tissue (AT) [2,[9][10][11][12][13]. In this regard, numerous studies have reported a strong relationship between adiposity and plasma leptin concentrations or its AT mRNA levels [14][15][16][17][18][19][20][21].…”
mentioning
confidence: 99%
“…Several studies have demonstrated that the leptin gene expression is positively regulated by insulin both in vivo (Saladin et al, 1995;Kolaczynski et al, 1996c) and in vitro (Kolaczynski et al, 1996c;Leroy et al, 1996). Plasma leptin levels decrease after fasting and increase by refeeding in humans (Kolaczynski et al, 1996a,b;Boden et al, 1996;Dubuc et al, 1998;Geldszus et al, 1996;Wadden et al, 1998) and rodents (Frederich et al, 1995), which parallels the change in plasma insulin levels (Kolaczynski et al, 1996b).…”
Section: Clinical Implications Of Leptinmentioning
confidence: 96%